Analisis Efisiensi Bank Umum Syariah di Indonesia (Studi Kasus Metode Stokastik Frontier) - Akhmad Afandi; Suhel Suhel; Ahmad Syathiri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The performance appraisal parameters of a bank are theoreticall can be seen from the level of efficiency of the bank. The efficiency of a bank will be identified from the bank's ability to produce maximum output with the most effective utilization of inputs. This study had analyzed the efficiency of Bank Umum Syariah (BUS) in Indonesia using the frontier stochastic method. The sample in the study was Bank Umum Syariah (BUS) in Indonesia with the research data analyzed in 2019 and 2020. The model used model fixes the model. The results of the analysis illustrate that Bank Umum Syariah (BUS) in Indonesia have a very good level of efficiency on inputs in the form of third party funds and labor costs with outputs in the form of financing. This study shows ROA, FDR and BOPO have a significant effect on efficiency both jointly and partially.